Penerimaan Mahasiswa Prodi Tiongkok UAI terhadap Ujian New HSK dan Pengaruhnya dalam Pembelajaran Bahasa Mandarin - Sri Hartati; Nanda L Qadriani; Zahrotun Nissa El laily (Universitas Al Azhar Indonesia, 2023)
HSK (Chinese Profession Test) is a standardized international Mandarin test. It was first introduced in 1991 and underwent a change in the exam system in 2009 to become the New HSK. Along with the development of teaching Mandarin in Indonesia, the need for the New HSK exam is increasing. The Chinese language and Chinese culture study program UAI (China Study Program), stipulates the use of the New HSK level 4 certificate as a diploma companion certificate as well as a graduation requirement for Chinese Study Program students. However, in practice, there are still students who are constrained in taking this exam. This study aims to see the extent to which Chinese Study Program students' acceptance of the New HSK exam and its effect on their Mandarin teaching. By using qualitative methods, data collection was carried out through a questionnaire distributed to 68 Chinese study program students. From the results of data processing, it is known that the acceptance and understanding of Chinese Study Program students towards the New HSK exam is quite good. The level of student participation in this exam is also quite high. The thing that becomes an obstacle for students is the lack of preparation to take the exam so that most of them decide to postpone the exam even before the thesis exam is held. For this reason, a better HSK preparation class is needed and increases the synergy between classroom learning and the New HSK.Keywords – Acceptance, New HSK, China Study Program.